Factors influencing caesarean section delivery in women with one previous lower segment caesarean section - Hazman, Wan Nur Hajidah W Mohd (2018)
Introduction: Caesarean deliveries is becoming a worldwide concern as the rate is kept widespread globally. One of the biggest contributions to the rising caesarean section rate was women with one previous caesarean section. The aim of the study was to assess the proportion and its associated factors of the mode of delivery among women with one previous lower segment caesarean section (LSCS) at Hospital USM, Kubang Kerian. Methods: A retrospective cohort study was conducted at Hospital USM involved retrospective records review of women with one previous LSCS who follow up and delivered their current pregnancy at Hospital USM. All the information about patients regarding their socio-demographic, maternal, neonatal characteristics and the mode of delivery as outcome variable were extracted. The mode of delivery was categorised into two groups which were a vaginal delivery and emergency LSCS. Descriptive statistics and Multiple Binary Logistic Regression were applied using STATA SE 14. Results: The percentage of the mode of delivery were 50% of women had a vaginal delivery and 50% of emergency LSCS. Majority of the women who included in this study was Malay and their average height was 153.20. The most of primipara women had undergone emergency LSCS (82%). Factors associated with the caesarean section were history of vaginal delivery (Adjusted OR=2.71; 95% CI: 1.60, 4.60; p<0.001), fetal weight estimation (Adjusted OR=4.78; 95% CI: 2.45, 9.34; p<0.001) and the presence of meconium-stained liquor (Adjusted OR=2.40; 95% CI: 1.33, 4.35; p=0.004). Conclusion: Women who had no history of vaginal delivery, their estimated fetal weight more than 3500 grams and been stained by meconium liquor were more likely to give birth via emergency LSCS. Keywords: caesarean section, VBAC, TOLAC, history of vaginal delivery, estimated fetal weight, meconium stained liquor, logistic regression